Local Wisdom in Traditional Medicinal Plant Utilization: An Ethnobotanical Study in Sonraen Village, Kupang Regency - Nur Aini Bunyani; Eleonora A.P Hija; Abdonia Finmeta; Nardi Leo (Jurnal Penelitian Pendidikan IPA, 2026)
This study aimed to document the diversity of traditional medicinal plants, plant parts used, preparation methods, and their medicinal applications by the community of Sonraen Village, Amarasi Selatan District, Kupang Regency, Indonesia. A descriptive ethnobotanical approach was employed through field observations, semi-structured interviews, documentation, and exploratory surveys involving knowledgeable local informants. A total of 51 medicinal plant species were recorded. Leaves were the most frequently used plant part, followed by rhizomes, stems, shoots, roots, bark, flowers, fruits, and seeds. Boiling was the predominant preparation method, while pounding, brewing, and direct application were also commonly practiced. The species with the highest citation values included Chromolaena odorata, Phyllanthus niruri, Curcuma longa, and Annona squamosa. These plants were primarily used to treat gastrointestinal disorders, hypertension, kidney disease, diabetes, malaria, wounds, and skin diseases. The findings demonstrate that traditional medicinal knowledge remains well preserved within the Sonraen community. This study provides baseline ethnobotanical data that support biodiversity conservation, preservation of indigenous knowledge, and future pharmacological investigations of medicinal plant species with high local use values.